"Making better use of U.S. women" Psychology, sex roles, and womanpower in post‐WWII America. Issue 3 (26th May 2017) - Rutherford, Alexandra
Abstract: The relationship between American psychology and gender ideologies in the two decades following World War II was complicated and multivalent. Although many psy‐professionals publicly contributed to the cult of domesticity that valorized women's roles as wives and mothers, other psychologists, many of them women, reimagined traditional sex roles to accommodate and deproblematize the increasing numbers of women at work, especially working mothers. In this article, I excavate and highlight the contributions of several of these psychologists, embedding their efforts in the context of the paradoxical expectations for women that colored the postwar and increasingly Cold War landscape of the United States. By arguing that conflict was inherent in the lives of both women and men, that role conflict (when it did occur) was a cultural, not intrapsychic, phenomenon, and that maternal employment itself was not damaging to children or families, these psychologists connected the work of their first‐wave, first‐generation forebears with that of the explicitly feminist psychologists who would come after them.